Application of bio-stimulants and Bacillus subtilis in the germination and initial development of corn culture - Buchelt, Antonio Carlos [UNESP]; Metzler, Carlos Renato; Castiglioni, Jose Lucas; Dassoller, Tiago Ferrarezi; Lubian, Matheus Sergio (Univ Estadual Mato Grosso Sul, 2019)
The study aimed to evaluate the germination and initial growth of the corn submitted to seed treatment with biostimulants (ProGibb 400 (R) and Stimulate (R)) and Bacillus subtilis. The experiment was carried out in the Technology and Seed Laboratory of the State University of Mato Grosso, Campus de Alta Floresta-MT. Completely randomized design, with ten treatments and four replications of 25 seeds each, were used. The treatments were Control, ProGibb 400 (R) 1, 2 and 3, with respective doses of 25, 50 and 75 mg kg-1 of seeds, Stimulate (R) 1, 2 and 3, with respective doses of 5, 10 and 15 mL kg-1 of seeds, and Bacillus subtilis 1, 2 and 3, with respective doses of 4, 6 and 8 mL kg-1 of seeds. Germination, shoot length, root length, and fresh and dry matter of shoots and roots were evaluated. The application of biostimulants and Bacillus subtilis did not influence the germination, root length, total length, shoot fresh matter and root dry matter of corn plants. The application of ProGibb 400 (R) increases the shoot length and dry matter of corn plants at the beginning of growth.
Keywords: Zea mays; plant hormone; seed treatment; technology